Criminal liability for vessel-source pollution in China: Law and practice - LIU, Nengye (Institutional Knowledge at Singapore Management University, 2013)
This article addresses criminal liability for vessel-source pollution in China. It describes relevant Chinese legislation regarding criminal liability for vessel-source pollution, analyses why a criminal case pertaining to vessel-source pollution has yet to be brought in Chinese courts and presents suggestions on how to improve the current regime.